2022
DOI: 10.1039/d2ta01952c
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective and ultrafast uptake of uranium from seawater by layered double hydroxide co-intercalated with acetamidoxime and carboxylic anions

Abstract: Through swelling/restoration reaction, acetamidoxime (ACAO) and the hydrolysates of carboxylic anions are co-intercalated into MgAl-LDH interlayers to generate a new material of ACAO-AC-LDH. The as-formed ACAO-AC-LDH displays outstanding capture capability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Furthermore, long alkyl chain surfactant, sodium dodecyl sulfate (SDS), is co-intercalated into LDHs together with PBA and then the SDS species prevent from the aggregation of PB in the interlayer region (marked as SDS-PBA@LDHs). [29][30][31] The structural and photophysical properties of different series LDHs are analyzed using various techniques. In the range of pH value from 7 to 10, specifically, LDHs exhibited excellent stability towards water.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, long alkyl chain surfactant, sodium dodecyl sulfate (SDS), is co-intercalated into LDHs together with PBA and then the SDS species prevent from the aggregation of PB in the interlayer region (marked as SDS-PBA@LDHs). [29][30][31] The structural and photophysical properties of different series LDHs are analyzed using various techniques. In the range of pH value from 7 to 10, specifically, LDHs exhibited excellent stability towards water.…”
Section: Introductionmentioning
confidence: 99%
“…Uranium (U) present in wastewaters produced via its mining, processing, and use in the nuclear fuel cycle is a significant environmental concern , with a range of potential ecotoxicological effects identified. , This includes the presence of U in the remediation of contaminated solutes produced during various processes associated with the nuclear fuel cycle, including U-mining, effluents from spent nuclear fuel reprocessing, nuclear fuel storage facilities, , U enrichment sites that are subject to decommissioning, , or cleanup procedures following the nuclear accidents. , To address these challenges, and especially when other radionuclides including transuranics such as plutonium and americium isotopes, and fission products including 90 Sr and 137 Cs may also be present, several studies have investigated U capture using various materials including layered double hydroxides (LDHs) formed in situ or prefabricated LDHs as adsorbents. , …”
Section: Introductionmentioning
confidence: 99%
“…As a clay-like material, layered double hydroxides (LDHs) have been extensively researched in recent years for heavy metal removal. LDHs typically have the general formula [(M 2+ ) 1– x (M 3+ ) x (OH) 2 ] x + (A m – ) x / m · n H 2 O] and a layered structure consisting of M 2+ and M 3+ cations octahedrally coordinated by oxygen in positively charged sheets, and anions (A m – ) and water in the interlayer region between the sheets. The LDH structure can accommodate a wide range of divalent and trivalent cations; hence through isomorphous substitution processes, LDHs can offer excellent removal performance for certain heavy metal ions (like Cd 2+ , Ni 2+ , and Cu 2+ ions) leading to superstable mineralization structures (SSMS). Recently, we reported that CaAl-LDH could be used as a mineralizer to selectively remove Cd 2+ ions from water with a capacity of 592 mg/g via isomorphous substitution to form a SSMS CdAl-LDH .…”
Section: Introductionmentioning
confidence: 99%